Legal Aspect Of Taxation: Prioritizing the Regularend Function of the Budgeter for National Economic Resilience - Syahyu, Yulianto (Jurnal Dinamika Hukum, 2023)
The Job Creation Law which has been approved and ratified becomes Law Number 11 of 2020, cannot be separated from the taxation cluster. As it is known that taxes have a budgetary function as state revenue and regulating function as a reflection of the country's economic policy. This study aims to examine the priority of the regularend function of taxes in the taxation cluster in Law Number 11 of 2020 concerning Job Creation. The results of the study indicate that the regularend function of taxes accommodated in the Job Creation Law and Perppu Number  1 year 2020 Jo. Law Number 2 of 2020 as well as Law Number 7 of 2021 concerning Tax Harmonization can work in several ways, namely: in the context of funding investment in Indonesia, tax incentives on dividends from within the country are intended to reduce the tax burden that must be borne by taxpayers, differences in interpretation in determining the status of tax subjects affect the country or jurisdiction that has the right to impose, relaxation of provisions for crediting Input Tax, which is deemed unfair for business actors, Arrangements on the amount of administrative sanctions of interest and interest compensation which are applied by taking into account market interest rates; and Taxation of digital transactions carried out by foreign sellers or marketplaces.